Laminate and coated structure
By applying a thin layer structure of heat absorption and heat release layer on wood and fiber-reinforced plastic substrates, the problem of heavy existing fireproof layer is solved, lightweight and efficient fireproofing effect is achieved, and the safety and fire resistance of the structure are improved.
Patent Information
- Application Number
- JP2024119358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-26
- Filing Date
- 2024-07-25
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2044-07-25
AI Technical Summary
The fire-proof layer of existing wood and fiber-reinforced plastic substrates is thick, which leads to inconvenience in construction and increases structural burden. At the same time, it is easy to burn in high temperature environments, affecting structural stability and safety.
A new laminated material consisting of a heat-absorbing layer and an exothermic layer, wherein the heat-absorbing layer consists of a sodium molybdate-containing adhesive, combined with a light filler and an expanded material, forms a thin layer structure to improve fire resistance.
It realizes lightweight and efficient fire protection of materials, reduces construction burden, improves the safety and fire resistance of the structure, and effectively suppresses temperature rise in high temperature environments.
Smart Images

Figure 2025019021000004 
Figure 2025019021000005 
Figure 2025019021000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate including a heat absorbing layer and a thermally foamable layer, and to a coated structure in which an organic substrate is coated with the laminate. [Background technology]
[0002] 2. Description of the Related Art Conventionally, concrete has been widely used for the structural framework (columns, beams, floors, foundations) of buildings, and civil engineering structures such as tunnels and bridges.
[0003] Although such concrete structures are generally said to have a service life of about 50 years, they can be damaged and deteriorated earlier due to disasters such as earthquakes.In addition, because concrete itself has a large mass, there are concerns that it could become a factor in causing human casualties in the event of a disaster.
[0004] Organic base materials such as wood and plastic are used in various structures as substitutes for concrete. In particular, wood base materials such as CLT (Cross Laminated Timber) and fiber-reinforced plastic base materials have attracted attention for their use in various structures due to their excellent specific strength.
[0005] However, organic substrates have the property that they are easily burned, deformed, lose strength, etc. when exposed to high temperatures, so they are required to be fire-resistant against fires that may occur during disasters.
[0006] For example, if organic base materials are used in the structural framework of a building, the heat of a fire may cause the organic base materials to burn or deform, significantly reducing their strength and leading to the collapse of the building.
[0007] In Patent Document 1, a laminate of gypsum board, panel insulation material (such as phenol foam), and non-combustible material (such as calcium silicate board) is used for the wood material to improve the fire resistance of the wood material. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent Publication No. 2019-150389 Summary of the Invention [Problem to be solved by the invention]
[0009] However, the laminate specifically disclosed in Patent Document 1 has a large overall thickness, and inorganic non-combustible materials such as gypsum boards and calcium silicate boards, which account for most of the thickness, have a large specific gravity, so the laminate has a heavy mass per unit area, is poor in workability and workability during transportation and construction, and may induce accidents, and the load between the base materials used is large, which is problematic. In addition, because the laminate is thick, if it is used for columns or walls, it may compress the room volume. Furthermore, if it is used for floor panels, it may lead to a narrower floor height, which may hinder facility planning.
[0010] Therefore, the problem that the present invention aims to solve is to provide a laminate that can be made thin and lightweight by using a laminate including a heat absorption layer and a thermal foaming layer made from specific raw materials, and that has excellent workability, safety, and fire resistance, and to provide a coated structure in which an organic substrate is coated with the laminate. [Means for solving the problem]
[0011] Therefore, the inventors conducted intensive research to solve the above problems, and discovered that by using a laminate including a heat absorption layer and a thermal foaming layer, in which the heat absorption layer is formed from a binder and sodium tetraborate, it is possible to reduce the thickness and weight, and the laminate is excellent in workability, safety, and fire resistance, thereby completing the present invention.
[0012] That is, the present invention has the following features. 1. A laminate including a heat absorbing layer and a thermal foaming layer, the heat absorbing layer being formed from a binder and sodium tetraborate. 2. The laminate described in 1., wherein the binder is an organic binder and the sodium tetraborate includes sodium tetraborate decahydrate. 3. The laminate according to 2., wherein the organic binder is obtained from a polyol and an isocyanate. 4. The laminate according to 2., wherein the organic binder is obtained from an unsaturated polyester and an unsaturated monomer. 5. The laminate according to 1., wherein the heat absorbing layer includes at least a heat absorbing layer formed from an organic binder and sodium tetraborate, and a heat absorbing layer formed from an inorganic binder. 6. The density of the heat absorbing layer is 0.05 g / cm 3 More than 1.5g / cm 3 The laminate according to 1., wherein the thickness is less than 1 mm. 7. The laminate according to 1, wherein the thickness of the laminate is 60 mm or less. 8. The mass per unit area of the laminate is 40 kg / m 2 The laminate according to 1. below. 9. A coated structure in which an organic substrate is coated with the laminate according to any one of 1. to 8. 10. The covered structure according to 9., wherein the organic substrate is a wood substrate and / or a plastic substrate. 11. The coated structure according to 9, wherein the heat absorbing layer and the organic substrate are in contact with each other. 12. The coated structure according to 9, wherein the organic substrate is a flat plate or a shaft-shaped member having a rectangular or circular cross section. Effect of the Invention
[0013] INDUSTRIAL APPLICABILITY The laminate of the present invention can be made thin and lightweight, and is excellent in workability, safety, and fire resistance, making it useful. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is an example of a model diagram (cross-sectional view) showing a covered structure of the present invention. [Diagram 2] FIG. 2 is an example of a model diagram (cross-sectional view) showing a covered structure of the present invention. [Diagram 3] FIG. 2 is an example of a model diagram (cross-sectional view) showing a covered structure of the present invention. [Figure 4] FIG. 2 is an example of a model diagram (cross-sectional view) showing a covered structure of the present invention. [Diagram 5] FIG. 2 is an example of a model diagram (cross-sectional view) showing a covered structure of the present invention. [Figure 6] FIG. 2 is a cross-sectional view showing a laminate of Example 1-1. [Figure 7] FIG. 2 is a cross-sectional view showing a laminate of Example 1-2. [Figure 8] FIG. 2 is a cross-sectional view showing a laminate of Example 1-3. [Figure 9] FIG. 2 is a cross-sectional view showing a laminate of Example 1-4. [Figure 10] FIG. 2 is a cross-sectional view showing a laminate of Example 1-5. [Figure 11] FIG. 2 is a cross-sectional view showing a laminate of Example 1-6. [Figure 12] FIG. 2 is a cross-sectional view showing a laminate of Example 1-7. [Figure 13] FIG. 2 is a cross-sectional view showing a laminate of Example 1-8. [Figure 14] FIG. 2 is a cross-sectional view showing a laminate of Example 1-9. [Figure 15] FIG. 2 is a cross-sectional view showing a laminate of Comparative Example 1-1. [Figure 16] FIG. 2 is a cross-sectional view showing a laminate of (Comparative Example 1-2). [Figure 17] FIG. 2 is a cross-sectional view showing a covering structure of (Example 2-1). [Figure 18] FIG. 2 is a cross-sectional view showing a covering structure of Example 2-2. [Figure 19] FIG. 4 is a cross-sectional view showing a covering structure of Example 2-3. [Figure 20] FIG. 4 is a cross-sectional view showing a covering structure of Example 2-4. [Figure 21] FIG. 4 is a cross-sectional view showing a covering structure of Example 2-5. [Figure 22] FIG. 4 is a cross-sectional view showing a covering structure of Example 2-6. [Figure 23]FIG. 4 is a cross-sectional view showing a covering structure of Example 2-7. [Figure 24] FIG. 4 is a cross-sectional view showing a covering structure of (Example 2-8). [Diagram 25] FIG. 2 is a cross-sectional view showing a covering structure of (Comparative Example 2-1). [Figure 26] FIG. 2 is a cross-sectional view showing a covering structure of (Comparative Example 2-2). [Figure 27] FIG. 4 is a cross-sectional view showing a covering structure of (Comparative Example 2-3). [Figure 28] FIG. 3 is a cross-sectional view showing a coated structure in which the organic substrate of Example 3-1 is a rectangular pillar. [Figure 29] FIG. 3 is a cross-sectional view showing a coated structure in which the organic substrate of Example 3-1 is a rectangular pillar. [Diagram 30] FIG. 3 is a cross-sectional view showing a coated structure in which the organic substrate of Example 3-2 is a rectangular pillar. [Diagram 31] FIG. 3 is a cross-sectional view showing a coated structure in which the organic substrate of Example 3-2 is a rectangular pillar. [Diagram 32] FIG. 3 is a cross-sectional view showing a coated structure in which the organic substrate of Example 3-3 is a rectangular pillar. [Diagram 33] FIG. 3 is a cross-sectional view showing a coated structure in which the organic substrate of Example 3-3 is a rectangular pillar. [Diagram 34] FIG. 2 is a cross-sectional view showing a case where the organic substrate of the covering structure of the present invention is a rectangular pillar. [Diagram 35] FIG. 2 is a cross-sectional view showing a case where the organic substrate of the covering structure of the present invention is a rectangular pillar. [Diagram 36] FIG. 2 is a cross-sectional view showing a case where the organic substrate of the covering structure of the present invention is a rectangular pillar. [Figure 37] FIG. 2 is a cross-sectional view showing a case where the organic substrate of the covering structure of the present invention is a rectangular pillar. [Explanation of symbols]
[0015] 1: Organic base material (base material 11~12) 2A: Endothermic layer (A) (endothermic layer 2A1~2A8) 2B: Endothermic layer (B) (endothermic layer 2B1~2B3, 2Ba, 2Bb) 3: Thermal foam layer (thermal foam layers 31-32) 4: Laminate (heat absorbing layer (A), heat absorbing layer (B), thermal foam layer) 5: Decorative layer P: Composite layer (endothermic layer (A), endothermic layer (B)) Q: Composite layer (heat absorbing layer (B), thermal foam layer) R: Composite layer (heat absorbing layer (A), thermal foam layer) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described.
[0017] [Laminate] The present invention relates to a laminate including a heat absorbing layer and a thermally foamable layer, the heat absorbing layer being formed from a binder and sodium tetraborate.
[0018] [Endothermic layer] The laminate of the present invention is a laminate including a heat absorbing layer, the heat absorbing layer being formed from a binder and sodium tetraborate. By using the binder, the sodium tetraborate can be fixed, and a heat absorbing layer having excellent heat absorbing properties and light weight can be formed.
[0019] The heat-absorbing layer may be one that exhibits a heat-absorbing effect when the temperature rises. Such a heat-absorbing layer, by virtue of a synergistic effect with a thermal foaming layer described later, prevents heat from being transferred to an organic substrate described later when the temperature rises during a fire or the like, and plays a role in maintaining the shape of the organic substrate. As a result, the covering structure in which the organic substrate is covered with the laminate has improved fire resistance and other properties due to the heat-absorbing effect of the heat-absorbing layer, making it useful.
[0020] (Binding Agent) The binder may be an organic binder or an inorganic binder. From the viewpoint of weight reduction, an organic binder is preferred, and from the viewpoint of heat absorption, an inorganic binder is preferred.
[0021] [Heat absorption layer (A)] In addition, it is preferable that the heat-absorbing layer includes at least an organic binder and a heat-absorbing layer formed of sodium tetraborate (hereinafter, sometimes referred to as "heat-absorbing layer (A)"). By using such a heat-absorbing layer (A), in addition to fire resistance, the weight of the entire laminate can be reduced, which is useful.
[0022] (Organic Binder) Examples of the organic binder include polyether resin, polyester resin, unsaturated polyester resin, vinyl acetate resin, alkyd resin, epoxy resin, acrylic resin, acrylic silicone resin, urethane resin, phenol resin, melamine resin, polycarbonate resin, fluororesin, acrylic-vinyl acetate resin, acrylic-urethane resin, acrylic-epoxy resin, silicone modified acrylic resin, ethylene-vinyl acetate resin, etc., and among them, from the viewpoint of weight reduction, it is preferable to use one obtained from polyol and isocyanate (the urethane resin obtained by reaction and hardening), or one obtained from unsaturated polyester and unsaturated monomer (the unsaturated polyester resin obtained by reaction and hardening). The urethane resin can reduce the density, so it is useful for reducing the weight of the laminate obtained, and the unsaturated polyester resin can reduce the thickness, so it is useful for reducing the weight of the laminate obtained.
[0023] (Polyol) Examples of the polyol include polyester polyol, polyether polyol, polycarbonate polyol, polylactone polyol, polybutadiene polyol, polypentadiene polyol, castor oil, castor oil-based polyol, and the like. One or more of these can be used.
[0024] Examples of the polyester polyol include aromatic polyester polyol, aliphatic polyester polyol, and aromatic / aliphatic polyester polyol.
[0025] Specifically, the aliphatic polyester polyol is a polyol having an aliphatic hydrocarbon in one molecule, and examples thereof include condensation polyester polyols obtained by reacting a saturated aliphatic polybasic acid such as succinic acid, adipic acid, azelaic acid, or sebacic acid with a polyhydric alcohol, and condensation polyester polyols obtained by reacting an unsaturated aliphatic polybasic acid such as maleic acid or fumaric acid with a polyhydric alcohol.
[0026] The aromatic polyester polyol is a polyol having an aromatic hydrocarbon in one molecule, and examples thereof include condensed polyester polyols obtained by reacting an aromatic polybasic acid such as orthophthalic acid, isophthalic acid, terephthalic acid, phthalic anhydride, etc. with a polyhydric alcohol, and phthalic acid-based polyester polyols obtained by decomposing a phthalic acid-based polyester molded product such as polyethylene terephthalate, etc. In addition, examples of the polyhydric alcohol include dihydric or higher alcohols and derivatives thereof, dihydric or higher phenols, polyols, etc.
[0027] The aromatic / aliphatic polyester polyol is a polyol having an aliphatic hydrocarbon and an aromatic hydrocarbon in one molecule, and examples thereof include condensation polyester polyols obtained by reacting an aromatic polybasic acid or an aliphatic polybasic acid with a polyhydric alcohol.
[0028] Examples of the polyether polyol include aromatic polyether polyols, phosphorus-containing polyether polyols, glycerin-based polyether polyols, and amino group-containing polyether polyols.
[0029] Examples of the aromatic polyether polyol include bisphenol A-type polyether polyols obtained by adding an alkylene oxide (e.g., ethylene oxide, propylene oxide, etc.) to bisphenol A as an initiator, and aromatic amine-based polyether polyols obtained by adding an alkylene oxide to an aromatic amine (e.g., toluenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylmethane, p-phenylenediamine, o-phenylenediamine, naphthalenediamine, triethanolamine, Mannich condensation products, etc.) as an initiator.
[0030] Examples of the phosphorus-containing polyether polyol include dialkyl-N,N-bis(2-hydroxyethyl)aminomethylphosphonate, which is a diol having a phosphoric acid ester structure.
[0031] The glycerin-based polyether polyols include polyether polyols obtained by adding alkylene oxide to glycerin as an initiator.
[0032] Examples of the amino group-containing polyether polyol include those obtained by adding an alkylene oxide to a low molecular weight amine (for example, ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, neopentyldiamine, etc.) as an initiator.
[0033] The castor oil-based polyol is a polymer derived from castor oil or castor oil fatty acid, and examples thereof include alkylene oxide adducts of castor oil or castor oil fatty acid, epoxidized products of castor oil or castor oil fatty acid, halides of castor oil or castor oil fatty acid, transesterification products of castor oil or castor oil fatty acid and polyhydric alcohol, and hydrogenated products thereof. In the present invention, castor oil-based polyols and / or castor oil are particularly preferred, and it is more preferred that they contain castor oil.
[0034] In particular, in the present invention, the polyol is preferably one containing a castor oil-based polyol and / or castor oil, and more preferably one containing castor oil.
[0035] The mixing ratio (mass ratio of solid contents) of the castor oil-based polyol to the castor oil is preferably 0:100 to 50:50, and more preferably 0:100 to 30:70.
[0036] The hydroxyl value of the polyol in the present invention is not particularly limited, but is preferably from 50 mgKOH / g to 500 mgKOH / g. The hydroxyl value is expressed as the number of milligrams of potassium hydroxide equivalent to the moles of hydroxyl groups contained in 1 g of sample, and is measured based on JIS K 1557-1:2007 Plastics - Test method for polyurethane raw material polyols - Part 1: Determination of hydroxyl value. The hydroxyl value of a polyol is the value measured for a mixture of all polyols.
[0037] (Isocyanate) The isocyanate has two or more isocyanate groups in one molecule and reacts with the polyol to form a molded product. Various isocyanates known in the polyurethane technical field can be used.
[0038] Examples of the isocyanate include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, etc., and derivatives thereof by allophanation, biuretization, dimerization (uretidione), trimerization (isocyanurate), adductization, carbodiimide reaction, etc., mixtures thereof, and copolymers thereof with monomers copolymerizable therewith, etc. These can be used alone or in combination of two or more.
[0039] Examples of the aliphatic diisocyanate include 1,3-trimethylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,3-pentamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate (HMDI), 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, and 1,3-butylene diisocyanate. anate, 2-methyl-1,5-pentamethylene diisocyanate, 3-methyl-1,5-pentamethylene diisocyanate, 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 2,6-diisocyanate methyl caproate, lysine diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate.
[0040] Examples of the alicyclic diisocyanate include 1,3-cyclopentane diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, isophorone diisocyanate (IPDI), norbornane diisocyanate, dicyclohexylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, and hydrogenated xylylene diisocyanate.
[0041] Examples of the aromatic diisocyanate include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate (TDI), 2,6-tolylene diisocyanate (TDI), naphthylene-1,4-diisocyanate, naphthylene-1,5-diisocyanate, 4,4'-diphenyl diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 2,4'-diphenylmethane diisocyanate, Examples of the isocyanate include 4,4'-diphenyl ether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, dianisidine diisocyanate, and tetramethylene xylylene diisocyanate.
[0042] Examples of the aromatic aliphatic diisocyanate include 1,3-xylylene diisocyanate (XDI), 1,4-xylylene diisocyanate (XDI), ω,ω'-diisocyanate-1,4-diethylbenzene, 1,3-bis(1-isocyanate-1-methylethyl)benzene, 1,4-bis(1-isocyanate-1-methylethyl)benzene, and 1,3-bis(α,α-dimethylisocyanate methyl)benzene.
[0043] In the present invention, it is particularly preferable to use aliphatic diisocyanates such as HMDI and its derivatives, aromatic diisocyanates such as MDI and its derivatives, etc. Furthermore, in the present invention, it is preferable to use trimerized (isocyanurated) aliphatic diisocyanates or aromatic diisocyanates, and in particular, it is preferable to use trimerized (isocyanurated) aliphatic diisocyanates in the present invention.
[0044] In the present invention, the isocyanate index is preferably from 100 to 500 (more preferably from 105 to 400, and even more preferably from 110 to 300). By mixing the polyol and the isocyanate in such a range, a urethane resin having excellent heat resistance and a heat absorbing layer (heat absorbing layer (A)) using the urethane resin can be obtained. The isocyanate index is expressed as 100 times the value obtained by dividing the number of equivalents of isocyanate groups in an isocyanate by the total number of equivalents of active hydrogen in an active hydrogen-containing component (polyol). In addition, the water liberated from the hydrate of sodium tetraborate, which will be described later, is not counted as an active hydrogen-containing component used in the above isocyanate index.
[0045] (Unsaturated polyester) The unsaturated polyester may be, for example, one produced by an esterification reaction between a polyhydric alcohol and a polybasic acid.
[0046] Examples of the polyhydric alcohol include alkylene glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, and neopentyl glycol, trimethylolethane, trimethylolpropane, glycerin, pentaerythritol, 1,6-hexanediol, ester glycol, 1,4-cyclohexanedimethanol, and 1,3-butanediol, and these can be used alone or in combination of two or more.
[0047] Examples of the polybasic acid include unsaturated polybasic acids such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, and citraconic acid. Phthalic acid (orthophthalic acid), isophthalic acid, terephthalic acid, phthalic anhydride, tetrahydrophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, cyclohexanedicarboxylic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, trimellitic acid, and pyromellitic acid can also be used in combination, and one or more of these can be used.
[0048] (Unsaturated Monomer) Examples of the unsaturated monomer include (meth)acrylic acid ester monomers such as methyl (meth)acrylate, and aromatic monomers such as styrene, methylstyrene, and divinylbenzene, and one or more of these can be used.
[0049] In the present invention, the mixing ratio of the unsaturated polyester and the unsaturated monomer is preferably 10 parts by mass or more and 200 parts by mass or less, more preferably 20 parts by mass or more and 180 parts by mass or less, relative to 100 parts by mass of the unsaturated polyester. By mixing the unsaturated polyester and the unsaturated monomer in such a range and, if necessary, adding an initiator, etc., it is possible to obtain an unsaturated polyester resin having excellent heat resistance and a heat absorbing layer (heat absorbing layer (A)) using the unsaturated polyester resin.
[0050] (Sodium tetraborate) The sodium tetraborate is a component that imparts endothermic properties. As the sodium tetraborate, from the viewpoint of endothermic properties, a hydrate of sodium tetraborate is preferable, sodium tetraborate pentahydrate and sodium tetraborate decahydrate are more preferable, and among them, sodium tetraborate decahydrate is particularly preferable from the viewpoint of excellent endothermic properties, since a large amount of hydration water is liberated from the hydrate and the temperature at which it is liberated is relatively low (about 60° C.).
[0051] The sodium tetraborate pentahydrate is a substance that releases water of hydration at temperatures from about 100 to 150°C. The sodium tetraborate decahydrate is a substance that releases water of hydration at temperatures from about 60°C. In addition, when the organic binder is a urethane resin, the sodium tetraborate hydrate is a component that can contribute to weight reduction by mixing the polyol and the isocyanate, and the water liberated from the sodium tetraborate hydrate reacts with the isocyanate to generate carbon dioxide and foam, and is also a component that contributes to the lightness of the heat absorption layer (heat absorption layer (A)).
[0052] The content of the sodium tetraborate is preferably 5% by mass or more and 90% by mass or less (further 10% by mass or more and 80% by mass or less, further 20% by mass or more and 70% by mass or less) of the entire heat-absorbing layer (A). Within such a range, a heat-absorbing layer (heat-absorbing layer (A)) that sufficiently combines heat absorption and light weight can be obtained.
[0053] The content of the sodium tetraborate in the heat absorbing layer (A) is 2.0 kg / m 2 or more (more preferably 2.5 kg / m 2 More than 20.0kg / m 2 Less than 3.0 kg / m, more preferably 3.0 kg / m 2 More than 15.0kg / m 2 Within such a range, it is possible to obtain a heat absorbing layer (heat absorbing layer (A)) that is sufficiently endowed with both heat absorbing properties and lightweight properties.
[0054] The amount of the sodium tetraborate mixed is preferably 5 parts by mass or more and 2000 parts by mass or less (more preferably 10 parts by mass or more and 1800 parts by mass or less, and even more preferably 20 parts by mass or more and 1500 parts by mass or less) relative to 100 parts by mass of the organic binder.
[0055] When the organic binder is a urethane resin, it is particularly preferable that the amount of sodium tetraborate mixed is 30 parts by mass or more and 2000 parts by mass or less (more preferably 50 parts by mass or more and 1800 parts by mass or less, and even more preferably 100 parts by mass or more and 1500 parts by mass or less) per 100 parts by mass of the polyol.
[0056] In the case where the organic binder is an unsaturated polyester resin, it is particularly preferable that the amount of the sodium tetraborate mixed is 40 parts by mass or more and 2000 parts by mass or less (more preferably 80 parts by mass or more and 1800 parts by mass or less, and even more preferably 120 parts by mass or more and 1500 parts by mass or less) per 100 parts by mass of the unsaturated polyester.
[0057] The heat absorbing layer (heat absorbing layer (A)) can be obtained by mixing other additives in addition to the above-mentioned components. Examples of the other additives include fillers, flame retardants, foaming agents, foam stabilizers, viscosity adjusters, hardening accelerators, initiators, metal hydrates, colorants, dyes, film-forming assistants, leveling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, surfactants, adsorbents, fibers, carbonizing agents, and solvents. In addition to the organic binder, the heat absorbing layer (A) can also contain an inorganic binder, which will be described later, as the binder to an extent that does not impair the effects of the present invention.
[0058] Examples of the filler include heavy calcium carbonate, kaolin, diatomaceous earth, white carbon, clay, talc, barite powder, precipitated barium sulfate, barium carbonate, silica sand, vermiculite, ceramic beads, glass beads, silica gel, perlite, expanded vermiculite, pumice, vermiculite, crushed ALC, hollow ceramic beads, hollow glass beads, shirasu balloons, charcoal, bamboo charcoal, seed shell charcoal, smoked seed shell charcoal, styrene resin foam, ethylene vinyl acetate resin foam, polyvinyl chloride resin foam, and the like. One or more of these may be used.
[0059] The amount of the filler to be mixed may be 10 parts by mass or more and 500 parts by mass or less (or even 20 parts by mass or more and 400 parts by mass or less) relative to 100 parts by mass of the organic binder. Within this range, excellent strength can be exhibited while ensuring light weight.
[0060] In particular, when the organic binder is a urethane resin, the amount of the filler to be mixed may be 30 parts by mass or more and 500 parts by mass or less (even more preferably 50 parts by mass or more and 400 parts by mass or less) relative to 100 parts by mass of the polyol. In this range, it is possible to ensure light weight while exhibiting excellent strength.
[0061] In particular, when the organic binder is an unsaturated polyester resin, the amount of the filler mixed may be 40 parts by mass or more and 500 parts by mass or less (even 80 parts by mass or more and 400 parts by mass or less) per 100 parts by mass of the unsaturated polyester.
[0062] In particular, in the present invention, the filler has a bulk density of 0.01 g / cm 3 More than 1g / cm 3 A lightweight filler having a mass of less than 10 ... Furthermore, in the present invention, one or more non-combustible lightweight fillers selected from perlite, expanded vermiculite, pumice, vermiculite, crushed ALC, ceramic hollow beads, hollow glass beads, charcoal, bamboo charcoal, seed shell charcoal, and smoked seed shell charcoal can be used.
[0063] The amount of the lightweight filler mixed is 300 parts by mass or less per 100 parts by mass of the organic binder. (Furthermore, 250 parts by mass or less) is sufficient. When the lightweight filler is in such a range, it is advantageous in terms of lightness and strength. Furthermore, when the lightweight filler is a non-combustible lightweight filler, it is also advantageous in terms of heat resistance.
[0064] In particular, when the organic binder is a urethane resin, the amount of the lightweight filler to be mixed may be 300 parts by mass or less (even 250 parts by mass or less) relative to 100 parts by mass of the polyol. The lightweight filler in this range is advantageous in terms of lightness and strength. In addition, when the lightweight filler is a non-flammable lightweight filler, it is also advantageous in terms of heat resistance.
[0065] In the case where the organic binder is an unsaturated polyester resin, the amount of the lightweight filler to be mixed may be 300 parts by mass or less (even 250 parts by mass or less) relative to 100 parts by mass of the unsaturated polyester. The lightweight filler in this range is advantageous in terms of lightness and strength. In addition, when the lightweight filler is a non-flammable lightweight filler, it is also advantageous in terms of heat resistance.
[0066] The bulk density of the filler is a value measured by supplying lightweight colored particles to a cylindrical container and applying up and down vibration (tapping vibration) until the bulk change of the lightweight colored particles in the container is completed.
[0067] The average particle size of the filler is not particularly limited, but may be from 50 μm to 1000 μm. The average particle size of the filler can be measured by a laser diffraction particle size distribution measuring device.
[0068] Examples of the flame retardant include phosphorus-based flame retardants, halogen-based flame retardants, boron-based flame retardants, metal hydroxide-based flame retardants, nitrogen-based flame retardants, and silicon-based flame retardants, and one or more of these can be used.
[0069] Examples of the phosphorus-based flame retardant include phosphate ester compounds, phosphate compounds, polyphosphate compounds, phosphite compounds, phosphonate compounds, phosphonite compounds, phosphinate compounds, phosphinate compounds, red phosphorus, phosphorus trichloride, and phosphorus pentachloride.
[0070] Specific examples of the phosphoric acid ester compound include trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, trisnonylphenyl phosphate, tributoxyethyl phosphate, tricresyl phosphate, cresyl phenyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, trixylenyl phosphate, diisopropyl phenyl phosphate, tris(2-ethylhexyl)phosphate, resorcinol bisdiphenyl phosphate, bisphenol A bis(diphenyl phosphate), resorcinol bisdixylenyl phosphate, tris(chloroethyl)phosphate, tris(chloropropyl)phosphate, tris(dichloropropyl)phosphate, bis(2, 3-dibromopropyl)-2,3-dichloropropyl phosphate, tris(2,3-dibromopropyl)phosphate, bis(chloropropyl)monoctyl phosphate, hydroquinonyl diphenyl phosphate, phenyl nonyl phenyl hydroquinonyl phosphate, phenyl dinonyl phenyl phosphate, diphenyl-4-hydroxy-2,3,5,6-tetrabromobenzyl phosphonate, dimethyl-4-hydroxy-3,5-dibromobenzyl phosphonate, diphenyl-4-hydroxy-3,5-dibromobenzyl phosphonate, trialkyl polyphosphate, resorcinol polyphenyl phosphate, bisphenol A polycresyl phosphate, resorcinol poly(di-2,6-xylyl)phosphate, hydroquinone poly(2,6-xylyl)phosphate, and the like.
[0071] Examples of the phosphate compound include aluminum phosphate, sodium phosphate, potassium phosphate, calcium phosphate, zinc phosphate, ammonium phosphate, aluminum phosphite, sodium phosphite, potassium phosphite, calcium phosphite, zinc phosphite, ammonium phosphite, aluminum hypophosphite, sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, zinc hypophosphite, ammonium hypophosphite, aluminum metaphosphate, sodium metaphosphate, potassium metaphosphate, calcium metaphosphate, and zinc metaphosphate.
[0072] Examples of the polyphosphate compound include ammonium polyphosphate, ammonium amide polyphosphate, melamine polyphosphate, piperazine polyphosphate, melem polyphosphate, melam polyphosphate, melon polyphosphate, and aluminum polyphosphate.
[0073] Examples of the phosphonate compound include methylphosphonic acid, dimethyl methylphosphonate, diethyl methylphosphonate, ethylphosphonic acid, propylphosphonic acid, butylphosphonic acid, 2-methylpropylphosphonic acid, t-butylphosphonic acid, 2,3-dimethyl-butylphosphonic acid, octylphosphonic acid, phenylphosphonic acid, and dioctyl phenylphosphonate.
[0074] Examples of the phosphinic acid salt compound include dimethylphosphinic acid, methylethylphosphinic acid, methylpropylphosphinic acid, diethylphosphinic acid, dioctylphosphinic acid, phenylphosphinic acid, diethylphenylphosphinic acid, diphenylphosphinic acid, and bis(4-methoxyphenyl)phosphinic acid.
[0075] The halogen-based flame retardants include, for example, those containing fluorine, chlorine, bromine, iodine, and antimony, and examples thereof include halogen oxides, halogenated phosphazenes, halogenated alkanes, halogenated indanes, halogenated phosphates, and halogenated polystyrenes.
[0076] Examples of the boron-based flame retardants include boron oxide, boric acid, lithium borate, sodium borate (excluding sodium tetraborate), potassium borate, cesium borate, magnesium borate, calcium borate, barium borate, zirconium borate, zinc borate, aluminum borate, and ammonium borate.
[0077] Examples of the metal hydroxide-based flame retardant include aluminum hydroxide, magnesium hydroxide, calcium hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, zinc hydroxide, titanium hydroxide, copper hydroxide, tin hydroxide, and vanadium hydroxide.
[0078] The amount of the flame retardant mixed is preferably 5 parts by mass or more and 1000 parts by mass or less (more preferably 10 parts by mass or more and 500 parts by mass or less, even more preferably 15 parts by mass or more and 200 parts by mass or less, still more preferably 20 parts by mass or more and 100 parts by mass or less, and most preferably 25 parts by mass or more and 80 parts by mass or less) relative to 100 parts by mass of the organic binder. By setting the amount of the flame retardant in such a range, it is possible to improve dispersibility and to achieve both heat resistance and light weight.
[0079] In the case where the organic binder is a urethane resin, the amount of the flame retardant mixed is preferably 10 parts by mass or more and 1000 parts by mass or less (more preferably 15 parts by mass or more and 500 parts by mass or less, even more preferably 20 parts by mass or more and 200 parts by mass or less, even more preferably 25 parts by mass or more and 100 parts by mass or less, and most preferably 30 parts by mass or more and 80 parts by mass or less) relative to 100 parts by mass of the polyol. By setting the amount of the flame retardant in such a range, it is possible to improve dispersibility and to achieve both heat resistance and light weight. In particular, it is preferable to use, as the polyol, a castor oil-based polyol and / or castor oil (more preferably castor oil) in the above-mentioned mixing ratio.
[0080] In the case where the organic binder is an unsaturated polyester resin, the amount of the flame retardant mixed is preferably 10 parts by mass or more and 1000 parts by mass or less (more preferably 15 parts by mass or more and 500 parts by mass or less, even more preferably 20 parts by mass or more and 200 parts by mass or less, even more preferably 25 parts by mass or more and 100 parts by mass or less, and most preferably 30 parts by mass or more and 80 parts by mass or less) relative to 100 parts by mass of the unsaturated polyester. By setting the amount of the flame retardant in such a range, it is possible to improve dispersibility and to achieve both heat resistance and light weight. In particular, it is preferable to use, as the unsaturated polyester, one produced by an esterification reaction between a polyhydric alcohol selected from ethylene glycol and propylene glycol and a polybasic acid selected from maleic acid, maleic anhydride, fumaric acid, and isophthalic acid, and to use, as the unsaturated monomer, a (meth)acrylic acid ester monomer and / or an aromatic monomer in the above-mentioned mixing ratio.
[0081] In the present invention, it is preferable to use the flame retardant and the sodium tetraborate in combination, which can improve the heat resistance, and in particular, by using a liquid flame retardant in combination, the dispersion stability of the sodium tetraborate and the viscosity of the composition can be controlled, and a heat absorbing layer having excellent heat resistance and light weight can be obtained.
[0082] The foaming agent is not particularly limited, but examples thereof include hydrofluoroolefins, hydrochlorofluoroolefins, water, liquefied carbon dioxide gas, etc., and one or more of these can be used.
[0083] Examples of the hydrofluoroolefin (HFO) include pentafluoropropenes such as 1,2,3,3,3-pentafluoropropene (HFO1225ye), tetrafluoropropenes such as 1,3,3,3-tetrafluoropropene (HFO1234ze), 2,3,3,3-tetrafluoropropene (HFO1234yf), and 1,2,3,3-tetrafluoropropene (HFO1234ye), and 3,3,3-trifluoropropene. Examples of suitable fluoropropenes include trifluoropropene (HFO1243zf), tetrafluorobutene (HFO1345), pentafluorobutene (HFO1354), hexafluorobutene (HFO1336), heptafluorobutene (HFO1327), heptafluoropentene (HFO1447), octafluoropentene (HFO1438), nonafluoropentene (HFO1429), and isomers thereof (cis isomer, trans isomer).
[0084] Examples of the hydrochlorofluoroolefin (HCFO) include 1-chloro-3,3,3-trifluoropropene (HCFO-1233zd), 2-chloro-3,3,3-trifluoropropene (HCFO-1233xf), dichlorotrifluoropropene (HCFO1223), and isomers thereof (cis isomer, trans isomer).
[0085] The blowing agent in the present invention is preferably one or more selected from hydrofluoroolefins, hydrochlorofluoroolefins, and water. For example, each blowing agent can be used in combination, such as hydrofluoroolefin and water, hydrochlorofluoroolefin and water, or hydrofluoroolefin, hydrochlorofluoroolefin and water.
[0086] In particular, when the organic binder is a urethane resin, the amount of the foaming agent mixed is preferably 200 parts by mass or less, more preferably 20 parts by mass or more and 180 parts by mass or less, and even more preferably 30 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of the polyol.
[0087] Examples of the foam stabilizer include silicone-based foam stabilizers such as polyether-modified silicone compounds, fluorine-containing compound-based foam stabilizers, etc. These may be used alone or in combination of two or more.
[0088] Examples of the polyether-modified silicone compound include graft copolymers of polydimethylsiloxane and polyoxyethylene glycol or polyoxyethylene-propylene glycol.
[0089] In particular, when the organic binder is a urethane resin, the amount of the foam stabilizer mixed is preferably 40 parts by mass or less, and more preferably 0.5 to 30 parts by mass, per 100 parts by mass of the polyol.
[0090] Examples of the viscosity regulator include layered clay minerals such as smectite and vermiculite, amide wax, hydrophobic cellulose such as ethyl cellulose and cellulose nitrate, and polyolefins such as polyethylene and polypropylene, and one or more of these can be used. In particular, in the present invention, it is preferable to use layered clay minerals, and it is particularly preferable to use layered clay minerals that have been organically treated with long-chain alkyl ammonium ions or the like (organic smectites (organic montmorillonite, organic bentonite, etc.), organic vermiculite, etc.).
[0091] In particular, when the organic binder is a urethane resin, the mixing amount of the viscosity modifier is preferably 60 parts by mass or less, and more preferably 1.0 to 40 parts by mass, relative to 100 parts by mass of the polyol.
[0092] Examples of the curing accelerator include amines such as triethylamine, triethylenediamine, triethylamine, tetramethylbutanediamine, dimethylaminoethanol, dimer diamine, and dimer acid polyamide amine; tin carboxylates such as dibutyltin dilaurate, dibutyltin diacetate, and tin octoate; metal carboxylates such as iron naphthenate, cobalt naphthenate, manganese naphthenate, zinc naphthenate, iron octylate, cobalt octylate, manganese octylate, and zinc octylate; carboxylates such as dibutyltin thiocarboxylate, dioctyltin thiocarboxylate, tributylmethylammonium acetate, and trioctylmethylammonium acetate; and aluminum compounds such as aluminum trisacetylacetate. One or more of these may be used.
[0093] In particular, when the organic binder is a urethane resin, the amount of the curing accelerator mixed is preferably 0.05 to 40 parts by mass, and more preferably 0.1 to 30 parts by mass, based on 100 parts by mass of the polyol.
[0094] Examples of the initiator include organic peroxides such as hydroperoxides, dialkyl peroxides, diacyl peroxides, ketone peroxides, peroxy esters, peroxy ketals, and peroxy dicarbonates; and azo compounds such as azobisisobutyronitrile, azobiscarbonamide, and 2-phenylazo-2,4-dimethyl-4-methoxyvaleronitrile. One or more of these can be used.
[0095] In particular, when the organic binder is an unsaturated polyester resin, the amount of the initiator mixed is preferably 0.05 to 10 parts by mass, and more preferably 0.1 to 80 parts by mass, based on 100 parts by mass of the unsaturated monomer.
[0096] The heat absorbing layer (A) may contain other metal hydrates in addition to the sodium tetraborate. Examples of such metal hydrates include sulfates such as ammonium aluminum sulfate dodecahydrate, sodium aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, magnesium sulfate dodecahydrate, sodium sulfate dodecahydrate, nickel sulfate dodecahydrate, zinc sulfate dodecahydrate, beryllium sulfate dodecahydrate, zirconium sulfate dodecahydrate, and other sulfates; sulfites such as zinc sulfite dihydrate and sodium sulfite dodecahydrate; aluminum phosphate dihydrate, cobalt phosphate octahydrate, magnesium phosphate octahydrate, and other sulfates; phosphates such as sium octahydrate, magnesium ammonium phosphate hexahydrate, magnesium hydrogen phosphate trihydrate, magnesium hydrogen phosphate heptahydrate, zinc phosphate tetrahydrate, and zinc dihydrogen phosphate dihydrate; nitrates such as aluminum nitrate nonahydrate, zinc nitrate hexahydrate, calcium nitrate tetrahydrate, cobalt nitrate hexahydrate, bismuth nitrate pentahydrate, zirconium nitrate pentahydrate, cerium nitrate hexahydrate, iron nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, and magnesium nitrate hexahydrate; acetates such as zinc acetate dihydrate and cobalt acetate tetrahydrate; chloride salts such as cobalt chloride hexahydrate and iron chloride tetrahydrate; and borates such as disodium octaborate tetrahydrate and zinc borate 3.5-hydrate.
[0097] The heat-absorbing layer (A) can be prepared by mixing the polyol, the isocyanate, and the sodium tetraborate, adding other additives as necessary, and curing the mixture to obtain the heat-absorbing layer (A) containing the urethane resin and the sodium tetraborate. In particular, a first liquid (first component) containing the polyol, the sodium tetraborate, and other additives as necessary, and a second liquid (second component) containing an isocyanate are prepared, and the first liquid and the second liquid are mixed and reacted to obtain the heat absorbing layer (A). The sodium tetraborate and other additives may be mixed only in the first component, or may be mixed in the second component as necessary. In such a case, it is particularly preferable to mix and react at a temperature of 10° C. or higher and 70° C. or lower (more preferably 15° C. or higher and 50° C. or lower).
[0098] The heat-absorbing layer (A) can be prepared by mixing the unsaturated polyester, the unsaturated monomer, and the sodium tetraborate, adding and mixing other additives as necessary, and curing the mixture to obtain the heat-absorbing layer (A) containing the unsaturated polyester resin and the sodium tetraborate. In particular, a first liquid (first component) containing the unsaturated polyester, the unsaturated monomer, and the sodium tetraborate, and other additives as necessary, and a second liquid (second component) containing an initiator are prepared, and the first liquid and the second liquid are mixed and reacted to obtain the heat absorbing layer (A). The sodium tetraborate and other additives may be mixed only in the first component, or may be mixed in the second component as necessary. In such a case, it is particularly preferable to mix and react at a temperature of 10° C. or higher and 70° C. or lower (more preferably 15° C. or higher and 50° C. or lower).
[0099] [Endothermic layer (B)] In addition, it is preferable that the heat absorption layer includes a heat absorption layer (hereinafter, sometimes referred to as "heat absorption layer (B)") formed by an inorganic binder in addition to the heat absorption layer (A). The heat absorption layer (B) is a heat absorption layer that does not contain (substantially does not contain) sodium tetraborate, unlike the heat absorption layer (A). Specifically, it is a heat absorption layer that does not contain (substantially does not contain) the organic binder (urethane resin, polyol and isocyanate constituting the urethane resin, unsaturated polyester resin, unsaturated polyester and unsaturated monomer constituting the unsaturated polyester resin) or sodium tetraborate (including sodium tetraborate decahydrate). Note that "substantially does not contain" refers to less than 5 mass% of the entire heat absorption layer (B).
[0100] (Inorganic binder) Examples of the inorganic binder include hydraulic inorganic binders, and among them, hydraulic inorganic binders are preferred from the viewpoint of heat absorption.
[0101] Examples of the hydraulic inorganic binder include portland cement, alumina cement, ultra rapid hardening cement, expansion cement, acidic phosphate cement, silica cement, lime mixed cement, blast furnace cement, fly ash cement, Keene's cement, magnesia cement, dolomite, calcium silicate, hydraulic lime, gypsum, etc., and one or more of these can be used.
[0102] The hydraulic inorganic binder can form a large amount of bound water during binding, and the heat absorbing layer It is possible to make (B) contain a large amount of bound water. As a result, when the temperature rises, it is possible to utilize the latent heat of vaporization of the bound water to exhibit excellent heat absorption. Furthermore, the heat absorption layer (B) containing the hydraulic inorganic binder is also excellent in strength, and the strength of the laminate of the present invention can be made excellent.
[0103] The heat absorbing layer (B) may contain other additives in addition to the inorganic binder. Examples of the other additives include water, fillers, water reducing agents, setting regulators, flame retardants, metal hydrates, fibers, adhesion improvers, water repellents, dispersants, surfactants, defoamers, and rust inhibitors. The organic binder may also be contained to the extent that it does not impair the effects of the present invention.
[0104] The heat-absorbing layer (B) can be obtained by mixing the inorganic binder and, if necessary, other additives, and curing the mixture. For example, the heat-absorbing layer (B) can be obtained by mixing the inorganic binder and other additives with water to form a kneaded mixture (slurry), curing and curing the mixture to form a heat-absorbing layer. (B) can be obtained. During the production, a reinforcing material such as a glass nonwoven fabric, a glass cloth, or a ceramic paper can be embedded.
[0105] Examples of such a heat absorbing layer (B) include cement board, reinforced cement board, glass fiber mixed cement board, calcium silicate board, glass fiber mixed calcium silicate board, gypsum board, reinforced gypsum board, glass fiber nonwoven fabric mixed gypsum board, and the like.
[0106] In the laminate of the present invention, a laminate of a plurality of heat absorbing layers, such as the heat absorbing layer (A) or the heat absorbing layer (B), can be used as the heat absorbing layer.
[0107] The method for laminating the multiple heat absorption layers is not particularly limited, but the heat absorption layers can be manufactured by a method (1) in which heat absorption layer (A) and heat absorption layer (B) are prepared in advance and then laminated using an adhesive or the like, a method (2) in which components constituting heat absorption layer (A) are poured so that they come into contact with heat absorption layer (B) prepared in advance and then hardened to form heat absorption layer (A), a method (3) in which components constituting heat absorption layer (B) are poured so that they come into contact with heat absorption layer (A) prepared in advance and then hardened to form heat absorption layer (B), or a method that combines these methods.
[0108] The methods (2) and (3) allow for adhesive-free lamination (direct lamination without using adhesive), and can suppress heat generation caused by the adhesive when exposed to high temperatures due to a fire, etc. For example, the method (2) has excellent adhesion.
[0109] Examples of the structure in which a plurality of heat absorption layers are stacked include a structure in which a plurality of heat absorption layers (A) are stacked, a structure in which heat absorption layers (A) and heat absorption layers (B) are stacked, and are not particularly limited. Examples of the structure include a structure in which heat absorption layers (A) / heat absorption layer (A), a structure in which heat absorption layers (A) / heat absorption layer (B), a structure in which heat absorption layers (B) / heat absorption layer (A) / heat absorption layer (B), a structure in which heat absorption layers (A) / heat absorption layer (B) / heat absorption layer (A), a structure in which heat absorption layers (B) / heat absorption layer ...) / heat absorption layer (B) / heat absorption layer (A), and a structure in which heat absorption layers (A) / heat absorption layer (B) / heat absorption layer (A) / heat absorption layer (A) / heat absorption layer (A) / heat absorption layer (A) / heat absorption layer (A) / heat absorption layer (A).
[0110] In addition, the heat absorption layer (A) may include a plurality of heat absorption layers (A) such as heat absorption layer (A1), heat absorption layer (A2), etc., which contain different raw materials other than the organic binder and sodium tetraborate or have different thicknesses, and the heat absorption layer (B) may include a plurality of heat absorption layers (B) such as heat absorption layer (B1), heat absorption layer (B2), etc., which contain different raw materials other than the inorganic binder or have different thicknesses.
[0111] The density of the heat absorbing layer (A) is 0.05 g / cm 3 More than 1.5g / cm 3 Less than (more preferably 0.08 g / cm 3 More than 1.2g / cm 3 Less than 0.1 g / cm, more preferably 0.1 g / cm 3 More than 1.0g / cm 3 It is preferable that The density of the heat absorbing layer (B) is 0.1 g / cm 3 More than 1.5g / cm 3 or less (more preferably 0.3 g / cm 3 More than 1.2g / cm 3 Less than 0.5 g / cm, more preferably 0.5 g / cm 3 More than 1.0g / cm 3 It is preferable that When the heat absorption layer (heat absorption layer (A) or heat absorption layer (B)) has such a density, it is possible to obtain a heat absorption layer that is lightweight yet excellent in heat resistance, strength, and dimensional stability.
[0112] In addition to the heat absorption layer (A), when the heat absorption layer (B) is included, the density of the entire heat absorption layer is 0.05 g / cm 3 More than 1.5g / cm 3 Less than (more preferably 0.08 g / cm 3 More than 1.2g / cm 3 Less than 0.1 g / cm, more preferably 0.1 g / cm 3 More than 1.0g / cm 3 It is preferable that
[0113] The thickness of the heat-absorbing layer (A) (one layer) is preferably 3 mm or more and 60 mm or less (more preferably 4 mm or more and 50 mm or less, even more preferably 5 mm or more and 30 mm or less, and most preferably 6 mm or more and 25 mm or less). The thickness of the heat-absorbing layer (B) (one layer) is preferably 1 mm or more and 50 mm or less (more preferably 3 mm or more and 30 mm or less, and further preferably 5 mm or more and 25 mm or less).
[0114] [Thermal foam layer] The laminate of the present invention includes a heat absorbing layer and a thermal foaming layer. The thermal foaming layer can be a layer that foams and forms a carbonized heat insulating layer by using the respective raw materials constituting the thermal foaming layer when the ambient temperature rises due to a fire or the like and the temperature of the thermal foaming layer reaches a predetermined foaming temperature.
[0115] The foaming temperature of the thermally foamable layer is preferably 150° C. or higher, more preferably 180° C. or higher, and further preferably 200 to 400° C., from the viewpoint of temperature rise due to flame, heat, and the like.
[0116] The thermally foamable layer can be formed, for example, from a thermally foamable coating material or a thermally foamable sheet, and these can be used alone or in a laminate of two or more kinds.
[0117] The thermally foamable layer is preferably made of a mixture of components including a resin component, a flame retardant, a foaming agent, a carbonizing agent, and a filler. Each of these components can be used alone or in combination of two or more.
[0118] Examples of the resin component include thermoplastic resins such as polyester resin, polybutadiene resin, acrylic resin, styrene resin, acrylic-styrene resin, vinyl acetate resin, vinyl acetate / vinyl ester of versatic acid copolymer resin, vinyl acetate / ethylene copolymer resin, vinyl acetate / vinyl ester of versatic acid / acrylic copolymer resin, vinyl acetate / acrylic copolymer resin, polyethylene resin, vinyl chloride resin, polypropylene resin, and polystyrene resin; and thermosetting resins such as epoxy resin, urethane resin, alkyd resin, phenol resin, and melamine resin.
[0119] Examples of the flame retardant include organic phosphorus compounds such as tricresyl phosphate and diphenyl cresyl phosphate; chlorine compounds such as chlorinated polyphenyl, chlorinated polyethylene, diphenyl chloride, triphenyl chloride, chlorinated paraffin, pentachlorinated fatty acid esters, perchloropentacyclodecane, chlorinated naphthalene, and tetrachlorophthalic anhydride; antimony compounds such as antimony trioxide and antimony pentachloride; phosphorus compounds such as phosphorus trichloride, phosphorus pentachloride, ammonium phosphate, ammonium polyphosphate, melamine phosphate, melamine polyphosphate, melam polyphosphate, melem polyphosphate, boron phosphate, boron polyphosphate, aluminum phosphate, and aluminum polyphosphate; and inorganic compounds such as zinc borate.
[0120] Examples of the foaming agent include melamine and its derivatives, dicyandiamide and its derivatives, azobistetrazole and its derivatives, azodicarbonamide, urea, and thiourea.
[0121] Examples of the carbonizing agent include pentaerythritol, dipentaerythritol, trimethylolpropane, starch, and casein.
[0122] Examples of the filler include talc, calcium carbonate, sodium carbonate, aluminum oxide (alumina), titanium oxide, zinc oxide, silica, clay, shirasu, mica, silica sand, silica powder, quartz powder, barium sulfate, and inorganic fibers.
[0123] The mixing ratio (mass ratio) of each of the components is preferably 200 to 600 parts by mass of the flame retardant, 40 to 150 parts by mass of the foaming agent, 40 to 150 parts by mass of the carbonizing agent, and 50 to 160 parts by mass of the filler, calculated as solid content, relative to 100 parts by mass of the resin component. When used at the above mixing ratio, flame retardancy, fire resistance, etc. can be satisfied, which is a preferred embodiment.
[0124] The mixture forming the thermally foamable layer may contain various additives, if necessary, in addition to the above-mentioned components. The additives may be any additives that do not significantly impair the effects of the present invention, and examples of such additives include pigments, fibers, wetting agents, plasticizers, lubricants, preservatives, antifungal agents, anti-algae agents, antibacterial agents, thickeners, dispersants, antifoaming agents, crosslinking agents, ultraviolet absorbers, light stabilizers, antioxidants, diluting solvents, etc.
[0125] The thermally foamable coating material used to form the thermally foamable layer can be used as a liquid mixture containing the above-mentioned components and additives. The thermally foamable sheet used to form the thermally foamable layer can be a mixture containing the above-mentioned components and additives formed into a sheet shape.
[0126] The thickness of the thermally foamed layer may be appropriately set depending on the application, etc., but from the viewpoints of fire resistance, lightweight, etc., it is preferably 0.1 to 10 mm, more preferably 0.3 to 8 mm, and further preferably 0.5 to 6 mm.
[0127] The thermally foamable layer may be composed only of a mixture containing the above-mentioned components and additives, but may also be a layer having a fibrous sheet or the like laminated on the front or back surface of the thermally foamable layer from the viewpoints of productivity, workability, flexibility, etc. As such a fibrous sheet, for example, a known sheet containing organic fibers and / or inorganic fibers can be used.
[0128] (Other layers) The laminate of the present invention includes (is laminated with) the heat absorbing layer and the thermally foamable layer, but may also include layers other than the above as necessary, as long as the effects of the present invention are not significantly impaired. Examples of such layers include an adhesive layer, a decorative layer, and other layers (e.g., a reinforcing layer, a heat reflective layer, a heat shielding layer, a waterproof layer, a water repellent layer, a water shielding layer, a heat insulating layer, etc.).
[0129] Among these, the adhesive layer is formed by an adhesive used when bonding each layer. The adhesive used in the adhesive layer can be a known adhesive such as a water-dispersed, water-soluble, or solvent-based adhesive made mainly of acrylic resin, silicon resin, epoxy resin, vinyl resin, phenolic resin, polyester resin, urethane resin, paraffin, or the like. The adhesive can be mixed with additives such as flame retardants, foaming agents, carbonizing agents, and fillers that are mixed with the above-mentioned thermal foaming layer, as necessary. In the present invention, the adhesive also includes a pressure-sensitive adhesive.
[0130] The decorative layer can be provided on the surface of the thermally foamed layer. For example, woodblocks, various coating materials, sheet materials, film materials, etc. can be used as the decorative layer. These can have various appearances such as transparent or opaque, colorless or colored, non-glossy or glossy, monochromatic or multicolored, flat or uneven, etc. In the present invention, the provision of the decorative layer is useful because it can improve the aesthetics, water resistance, weather resistance, etc. of the laminate of the present invention.
[0131] The heat reflection layer can be provided between the heat foaming layer and the heat absorption layer, or between the heat absorption layer and the organic base material. As the heat reflection layer, a metal plate, sheet, tape, etc. having high heat reflectivity can be used. Specific examples of the heat reflection layer include aluminum foil, aluminum tape, aluminum cloth, aluminum foil / glass nonwoven fabric laminated sheet, aluminum foil / mesh laminated sheet, aluminum foil / synthetic resin laminated sheet, etc.
[0132] By providing the heat reflecting layer between the heat foaming layer and the heat absorbing layer, the heat foaming layer can be foamed smoothly, and an excellent carbonized heat insulating layer can be formed.
[0133] The thickness of the heat reflective layer may be appropriately set depending on the application, etc., but from the standpoint of fire resistance, lightweight, etc., it is preferably 0.01 to 1 mm, more preferably 0.02 to 0.8 mm, and even more preferably 0.03 to 0.6 mm.
[0134] (Laminate properties) The laminate of the present invention can be made thinner than those of the conventional technology, and the thickness (total thickness) of the laminate is preferably 60 mm or less, more preferably 10 to 58 mm, and even more preferably 15 to 55 mm. When the thickness of the laminate is equal to or less than the upper limit of the above range, the burden on workers and the risk of injury during transportation and construction work can be reduced, and work efficiency can be improved. When the laminate is applied to indoor pillars, beams, floor slabs, walls, etc., it is also possible to expand the indoor space. When the thickness of the laminate is equal to or more than the lower limit of the above range, it is preferable in terms of heat insulation, fire resistance, strength, etc.
[0135] The mass per unit area of the laminate of the present invention is preferably 40 kg / m 2 Less than or equal to 10 to 35 kg / m 2 , and more preferably 15 to 30 kg / m 2Since the laminate having such characteristics is lightweight, it is possible to reduce the burden on workers and the risk of injury during transportation and construction work, and to improve work efficiency. Furthermore, after construction to an organic substrate, it is also possible to reduce the load on the organic substrate.
[0136] [Covering structure] The present invention relates to a coated structure in which an organic substrate is coated with the laminate. The coated structure is preferable because it has excellent fire resistance due to the organic substrate being coated with the laminate including the heat absorbing layer and the thermal foaming layer.
[0137] In addition, in the coated structure of the present invention, it is preferable that the heat absorption layer and the organic substrate are in contact with each other. When the heat absorption layer included in the laminate contacts the organic substrate, the temperature rise of the organic substrate can be suppressed during a temperature rise such as during a fire, and this is preferable because it has excellent fire resistance.
[0138] (Organic base material) Examples of the organic substrate include a wood substrate, a plastic substrate, a fiber-reinforced plastic substrate, a paper substrate, a fibrous substrate, or a substrate made by combining these. From the viewpoints of strength and light weight, a wood substrate, a plastic substrate, a fiber-reinforced plastic substrate, or a substrate made by combining these is preferable.
[0139] Examples of the wood substrate include lumber, plywood, laminated lumber, LVL (Laminated Veneer Lumber), CLT (Cross Laminated Timber), particle board, fiberboard, etc. The use of such wood substrates also contributes to the promotion of carbon neutrality.
[0140] Among the wood substrates, the CLT is called cross-laminated timber, which is a wood material in which sawn boards (lamina) are arranged and then laminated so that the fiber direction is perpendicular. Specifically, CLT is defined in the Japanese Agricultural Standard JAS3079:2019 "Cross-laminated timber" as "wood in which sawn boards or small square timbers (including those adjusted by joining and gluing them in the length direction with their fiber directions approximately parallel to each other) are arranged or glued in the width direction with their fiber directions approximately parallel to each other, and are laminated and glued mainly with their fiber directions approximately perpendicular to each other to have a structure of three or more layers." By using CLT as a wood substrate, it becomes possible to apply the laminate of the present invention to structural members (structural bodies), etc.
[0141] The thickness of the wood base material can be appropriately set depending on the application, etc.
[0142] As the plastic substrate, a substrate containing a thermoplastic resin and / or a thermosetting resin as a main component can be used.
[0143] Examples of the thermoplastic resin include polyamide, polyacetal, polysulfone, polyester, polybutylene terephthalate, polycarbonate, polyethylene terephthalate, polyethylene, polypropylene, polyphenylene sulfide, polyether ether ketone, polyether imide, polyether ketone ketone, polyvinyl chloride, acrylic resin, ABS resin, fluororesin, and silicone resin.
[0144] As the thermosetting resin, those that form a three-dimensional crosslinked structure by a crosslinking reaction can be used, and examples thereof include unsaturated polyester resins, vinyl ester resins, epoxy resins, benzoxazine resins, phenolic resins, urethane resins, urea resins, melamine resins, polyimide resins, etc. These can be used alone or in combination of two or more.
[0145] In the present invention, a fiber-reinforced plastic substrate can be used as the plastic substrate. The fiber-reinforced plastic substrate is a composite of the resin and fiber as described above, and is a substrate having properties such as high specific rigidity and high specific strength. By using a fiber-reinforced plastic substrate as the plastic substrate, it becomes possible to apply the laminate of the present invention to structural members (structural bodies) and the like.
[0146] Examples of the fibers used in the fiber-reinforced plastic substrate include glass fibers, aramid fibers, Kevlar fibers, carbon fibers, graphite fibers, boron fibers, Tyranno fibers, silicon carbide fibers, silicon nitride fibers, alumina fibers, and mineral fibers, and among these, glass fibers and carbon fibers are preferred from the viewpoint of improving mechanical strength, and glass fibers are also preferred from the viewpoint of cost. These can be used alone or in combination of two or more kinds.
[0147] The thickness of the plastic substrate can be appropriately set depending on the application.
[0148] Examples of the organic substrate include flat plates or axial members having a rectangular or circular cross section. Flat plates or axial members having a rectangular or circular cross section are preferred because they are frequently used in flooring materials, wall materials, columns (square columns, round columns, etc.) and beams, and have excellent workability.
[0149] Hereinafter, a covered structure in which the organic substrate (hereinafter sometimes simply referred to as "substrate") is covered with the laminate will be described with reference to the drawings.
[0150] 1 to 5 show an example (cross-sectional view) of the coated structure of the present invention. The heat absorption layer 2A and the like correspond to the heat absorption layer (A), and the heat absorption layer 2B and the like correspond to the heat absorption layer (B). The heat absorption layer 2Ba and the heat absorption layer 2Bb in FIG. 5 correspond to the heat absorption layer (B), and show that the heat absorption layer (B) has a plurality of layers.
[0151] In the covering structure of FIG. 1, the heat absorption layer 2A, the heat absorption layer 2B, and the thermal foaming layer 3 are laminated in this order on the organic substrate 1 as the laminate 4. That is, the heat absorption layer 2A side of the laminate 4 is fixed so as to contact the organic substrate 1. In the present invention, two or more materials can be laminated as materials constituting each layer. The covering structure provided with such a laminate 4 can exhibit excellent fire resistance. Specifically, when the thermal foaming layer 3 side is exposed to high temperatures due to a fire or the like, the heat absorption layer 2B exhibits a heat absorption effect, and the thermal foaming layer 3 foams to form a carbonized heat insulating layer, thereby suppressing the transfer of heat to the heat absorption layer 2A present inside, and the transfer of heat to the heat absorption layer 2B and the heat absorption layer 2A present inside is suppressed, and the shapes of the heat absorption layer 2B and the heat absorption layer 2A are maintained. The heat absorption layer 2A sufficiently suppresses the temperature rise of the organic substrate 1 due to its performance. In the present invention, the synergistic effect of these three layers can prevent the organic substrate 1 from burning, deforming, or losing its strength due to heat, and can exhibit excellent fire resistance.
[0152] The coated structure may be one in which the organic substrate 1 is a flat plate or a shaft-shaped member having a rectangular or circular cross section. Examples (cross-sectional views) of the coated structure of the present invention include the coated structures shown in Figures 28 to 37, in which the organic substrate 1 is a shaft-shaped member (prism) having a rectangular cross section.
[0153] As shown in the covering structure of Fig. 2, a laminate 4 may be formed by laminating a heat absorbing layer 2B, a heat absorbing layer 2A, and a thermally foamable layer 3 in this order on an organic substrate 1. In the covering structure of Fig. 2, the heat absorbing layer 2B side of the laminate 4 is fixed so as to contact the organic substrate 1. In the present invention, the synergistic effect of the three layers can prevent the organic substrate 1 from burning, deforming, or losing strength due to heat, and can exhibit excellent fire resistance.
[0154] When a wooden base material such as CLT or a fiber-reinforced plastic base material is used as the organic base material 1, it becomes possible to use it as a structural member (structural body) while taking advantage of the lightweight material characteristics. In particular, when a wooden base material such as CLT is used as the organic base material 1, it is also suitable in terms of promoting carbon neutrality.
[0155] As a method for forming the covering structure of the present invention, for example, the following method can be adopted. (1) A method of producing a laminate 4 having a heat absorption layer 2A, a heat absorption layer 2B, and a thermal foaming layer 3, or a laminate 4 having a heat absorption layer 2B, a heat absorption layer 2A, and a thermal foaming layer 3, and fixing the heat absorption layer 2A side or the heat absorption layer 2B side of the laminate 4 so that it is in contact with an organic substrate 1 (FIGS. 1 and 2). (2) A method of fixing the heat absorption layer 2A, the heat absorption layer 2B, and the thermal foaming layer 3 in order to the organic substrate 1, or a method of fixing the heat absorption layer 2B, the heat absorption layer 2A, and the thermal foaming layer 3 in order to the organic substrate 1 (Figures 1 and 2). (3) A method in which a composite layer P having a heat absorbing layer 2A and a heat absorbing layer 2B is produced in advance, the composite layer P is fixed to an organic substrate 1, and then a thermally foamed layer 3 is fixed (FIG. 3). (4) A method in which a composite layer Q having a heat absorption layer 2B and a thermally foamed layer 3 is produced in advance, a heat absorption layer 2A is fixed to an organic substrate 1, and then the composite layer Q is fixed; or a method in which a composite layer R having a heat absorption layer 2A and a thermally foamed layer 3 is produced in advance, a heat absorption layer 2B is fixed to an organic substrate 1, and then the composite layer R is fixed (Figure 4). (5) A method in which a composite layer P having a heat absorption layer 2A and a heat absorption layer 2Ba, and a composite layer Q having a heat absorption layer 2Bb and a thermally foamed layer 3 are each produced in advance, and the composite layer P is fixed to the organic substrate 1, and then the composite layer Q is fixed (Figure 5).
[0156] The above-mentioned layers, composite layers, and laminates can be fixed using, for example, fasteners such as nails, screws, rivets, pins, bolts, and staples, or adhesives, etc. The thermally foamable layer 3 can also be formed by, for example, painting a thermally foamable coating material on the surface of the heat-absorbing layer 2B (or the heat-absorbing layer 2A).
[0157] In the present invention, even if a thermally conductive material such as a metal fastener is used as the fastener, when the temperature rises during a fire or the like, the thermal foaming layer 3 foams and forms a carbonized insulating layer, thereby suppressing the thermal bridging effect of the fastener.
[0158] In the present invention, it is preferable that any or all of the above-mentioned layers, composite layers, and laminates are plate-shaped materials (plate materials). This can improve workability during construction. In particular, since the laminates of the present invention are lightweight, the covered structure of the present invention can be efficiently formed by one or two fixing steps. For example, the covered structure of the present invention can be formed in one step by the method (1) above, and in two steps by the methods (3) to (5) above.
[0159] When using plate materials in the above methods (2) to (5), the butt joints between the multiple plate materials constituting the lower layer (the joints of the lower layer) and the butt joints between the multiple plate materials constituting the upper layer (the joints of the upper layer) may be in the same position, but from the standpoint of improving fire resistance, it is desirable to shift the joints of the lower layer and the upper layer so that they are in different positions.
[0160] The thermally foamed layer 3 is provided on the surface of the heat-absorbing layer 2B (or the heat-absorbing layer 2A), but may also be provided on the side of the laminate. For example, when a plate material is used in the methods (1) to (5) above, by providing the thermally foamed layer 3 over the side of the plate material, the thermally foamed layer is also provided at the butt joints (joints) between multiple plate materials, thereby improving fire resistance.
[0161] The laminate of the present invention can be applied to applications requiring fire resistance, for example, in various fields such as architecture, civil engineering, ships, vehicles, aircraft, etc. When used as a building material, it can be applied to, for example, ceiling materials, roof materials, wall materials, floor materials, pillars, beams, eaves, doors, partitions, etc., and is particularly preferably applied to structural bodies such as wall materials, floor materials, pillars, beams, etc.
[0162] Furthermore, since the covered structure of the present invention is an organic substrate covered with the laminate, it has excellent fire resistance and the like, and can suppress the temperature of the surface of the organic substrate when the temperature rises during a fire, etc. EXAMPLES
[0163] The features of the present invention will be more clearly described below with reference to examples and comparative examples, but the present invention should not be construed as being limited to these examples.
[0164] The following materials were used as materials for constructing the laminate used as a test specimen.
[0165] Substrate 11: Wood substrate (organic substrate) (600mm x 450mm, thickness 25mm, plate-shaped) Substrate 12: Wood substrate (organic substrate) (210mm x 210mm, height 800mm, square column)
[0166] Decorative layer 5: Woodblock (thickness 10 mm, mass 3.8 kg / m 2 )
[0167] ·Heat absorbing layer 2A1 constituents: Endothermic layer 2A1 first component: Castor oil (hydroxyl value: 160 mg KOH / g, solid content 100% by mass) 28 parts by mass Sodium tetraborate decahydrate 58 parts by weight Tris(chloropropyl)phosphate (solid content 100% by mass) 14 parts by mass Dibutyltin dilaurate (solid content 100% by mass) 0.5 parts by mass Endothermic layer 2A1 second component HMDI polyisocyanurate (NCO%: 20, solids content 100% by mass) 25 parts by mass (Isocyanate index: 150)
[0168] · Endothermic layer 2A2 constituents: Endothermic layer 2A2 first component: Castor oil (hydroxyl value: 160 mg KOH / g, solid content 100% by mass) 28 parts by mass 58 parts by weight of sodium borate pentahydrate Tris(chloropropyl)phosphate (solid content 100% by mass) 14 parts by mass Dibutyltin dilaurate (solid content 100% by mass) 0.5 parts by mass Endothermic layer 2A2 second component HMDI polyisocyanurate (NCO%: 20, solids content 100% by mass) 25 parts by mass (Isocyanate index: 150)
[0169] · Endothermic layer 2A3 constituents: Endothermic layer 2A3 first component: Castor oil (hydroxyl value: 160 mg KOH / g, solid content 100% by mass) 28 parts by mass Aluminum hydroxide 58 parts by weight Tris(chloropropyl)phosphate (solid content 100% by mass) 14 parts by mass Dibutyltin dilaurate (solid content 100% by mass) 0.5 parts by mass Endothermic layer 2A3 second component HMDI polyisocyanurate (NCO%: 20, solids content 100% by mass) 25 parts by mass (Isocyanate index: 150)
[0170] ·Heat absorbing layer 2A4 constituents: Endothermic layer 2A4 first component Castor oil (hydroxyl value: 160 mgKOH / g, solid content 100% by mass) 18 parts by mass Castor oil-based polyol (hydroxyl value: 220 mg KOH / g, solid content 100% by mass) 10 parts by mass Sodium tetraborate decahydrate 58 parts by weight Tris(chloropropyl)phosphate (solid content 100% by mass) 14 parts by mass Dibutyltin dilaurate (solid content 100% by mass) 0.05 parts by mass Endothermic layer 2A4 second component MDI-based polyisocyanurate (NCO%: 20, solid content 100% by mass) 20 parts by mass (Isocyanate index: 160)
[0171] ·Heat absorbing layer 2A5 constituents: Endothermic layer 2A5 first component Castor oil-based polyol (hydroxyl value: 220 mg KOH / g, solid content 100% by mass) 10 parts by mass Sodium tetraborate decahydrate 67 parts by weight Tris(chloropropyl)phosphate (solid content 100% by mass) 30 parts by mass Dibutyltin dilaurate (solid content 100% by mass) 0.05 parts by mass Additive (dispersant) 3 parts by weight Heat absorbing layer 2A5 second component HMDI polyisocyanurate (NCO%: 20, solids content 100% by mass) 10 parts by mass (Isocyanate index: 190)
[0172] ·Heat absorbing layer 2A6 constituents: Endothermic layer 2A6 first component Terephthalic acid-based polyester polyol (hydroxyl value: 180 mgKOH / g, solid content 100% by mass) 9 parts by mass Sodium tetraborate decahydrate 40 parts by weight Tris(chloropropyl)phosphate (solid content 100% by mass) 58 parts by mass Dibutyltin dilaurate (solid content 100% by mass) 0.7 parts by mass Additives (silicone foam stabilizer, dispersant) 1 part by weight Endothermic layer 2A6 second component HMDI polyisocyanurate (NCO%: 20, solids content 100% by mass) 12 parts by mass (Isocyanate index: 180)
[0173] ·Heat absorbing layer 2A7 constituents: Endothermic layer 2A7 first component Unsaturated polyester resin (unsaturated polyester / styrene (mass ratio 60 / 40)) 50 parts by mass Sodium tetraborate decahydrate 50 parts by weight Endothermic layer 2A7 second component Methyl ethyl peroxide 1 part by mass
[0174] ·Heat absorbing layer 2A8 constituents: Endothermic layer 2A8 first component Unsaturated polyester resin (unsaturated polyester / styrene (mass ratio 58 / 42) 48 parts by mass Sodium tetraborate decahydrate 52 parts by weight Endothermic layer 2A8 second component Methyl ethyl peroxide 1 part by mass
[0175] Heat absorption layer 2B1: Glass fiber nonwoven fabric gypsum board (thickness 8 mm, mass 6.8 kg / m 2 ) Heat absorption layer 2B2: Glass fiber nonwoven fabric gypsum board (thickness 5 mm, mass 4.2 kg / m 2 ) Heat absorption layer 2B3: Glass fiber mixed gypsum board (thickness 12.5 mm, mass 11.0 kg / m 2 )
[0176] Thermally foamed layer 31: Thermally foamable sheet [a mixture of 100 parts by mass of thermoplastic resin (ethylene vinyl acetate copolymer resin-acrylic resin), 60 parts by mass of foaming agent (melamine), 60 parts by mass of carbonizing agent (pentaerythritol), 300 parts by mass of flame retardant (ammonium polyphosphate), 75 parts by mass of filler (titanium oxide), and other additives (fibers, plasticizers, etc.), kneaded in a kneader heated to 120°C, rolled, and then cooled to room temperature to obtain a thermally foamable sheet. Thickness: 1.1 mm, mass: 1.5 kg / m 2 ] Thermally foamed layer 32: Thermally foamable sheet [a mixture of 100 parts by mass of thermoplastic resin (ethylene vinyl acetate copolymer resin-acrylic resin), 60 parts by mass of foaming agent (melamine), 60 parts by mass of carbonizing agent (pentaerythritol), 300 parts by mass of flame retardant (ammonium polyphosphate), 75 parts by mass of filler (titanium oxide), and other additives (fibers, plasticizers, etc.), kneaded in a kneader heated to 120°C, rolled, and then cooled to room temperature. Thermally foamable sheet obtained. Thickness: 3 mm, mass: 4.2 kg / m 2 ]
[0177] Organic insulation layer: Flame retardant-containing polystyrene foam board (thickness 30 mm, thermal conductivity 0.038 W / (m K), density 40 kg / m 3, mass 1.2kg / m 2 , ISO-5660 (Radiant heat intensity 50kW / m 2 (burned for 5 minutes at 350°C) generates a total heat output of 8MJ / m 2 below)
[0178] · Acrylic resin adhesive (water-based reactive curing acrylic adhesive)
[0179] [Example 1-1] (Test specimen 1-1) The heat absorption layer 2B1 was placed in a formwork (100 mm x 100 mm), and a mixed liquid of the first constituent component of the heat absorption layer 2A1 and the second constituent component of the heat absorption layer 2A1 was poured onto the heat absorption layer 2B1. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then removed from the formwork to obtain a laminate of the heat absorption layer 2B1 and the heat absorption layer 2A1. Furthermore, a thermally foamable layer 31 was attached to the heat absorption layer 2B1 side of the laminate using an acrylic resin adhesive to obtain a test specimen 1-1. The content of sodium tetraborate hydrate in the heat absorption layer 2A1 was 4.2 kg / m 2 This specimen 1-1 has the configuration shown in FIG.
[0180] [Example 1-2] (Test specimen 1-2) The heat absorption layer 2B1 was placed in a formwork (100 mm x 100 mm), and a mixed liquid of the first constituent component of the heat absorption layer 2A2 and the second constituent component of the heat absorption layer 2A2 was poured onto the heat absorption layer 2B1. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then removed from the formwork to obtain a laminate of the heat absorption layer 2B1 and the heat absorption layer 2A2. Furthermore, a thermal foaming layer 31 was attached to the heat absorbing layer 2A2 side of the laminate using an acrylic resin adhesive to obtain a test specimen 1-2. The content of sodium tetraborate hydrate in the heat absorbing layer 2A2 was 4.2 kg / m 2 This specimen 1-2 has the configuration shown in FIG.
[0181] [Examples 1-3] (Test specimen 1-3) The heat absorption layer 2B1 was placed in a formwork (100 mm x 100 mm), a mixed liquid of the first constituent component of the heat absorption layer 2A1 and the second constituent component of the heat absorption layer 2A1 was poured onto the heat absorption layer 2B1, and the heat absorption layer 2B1 was laminated on top of that. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour, and then the mixture was removed from the mold to obtain a laminate of heat absorption layer 2B1 / heat absorption layer 2A1 / heat absorption layer 2B1. Furthermore, a thermal foaming layer 31 was attached to one surface of the laminate (heat absorbing layer 2B1 / heat absorbing layer 2A1 / heat absorbing layer 2B1) using an acrylic resin adhesive to obtain a test specimen 1-3. The content of sodium tetraborate hydrate in the heat absorbing layer 2A1 was 4.2 kg / m 2 This test specimen 1-3 has the configuration shown in FIG.
[0182] [Examples 1-4] (Test specimen 1-4) The heat absorption layer 2B1 was placed in a formwork (100 mm x 100 mm), a mixed liquid of the first constituent component of the heat absorption layer 2A4 and the second constituent component of the heat absorption layer 2A4 was poured onto the heat absorption layer 2B1, and the heat absorption layer 2B1 was laminated on top of that. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour, and then the mixture was removed from the mold to obtain a laminate of heat absorption layer 2B1 / heat absorption layer 2A4 / heat absorption layer 2B1. Furthermore, a thermal foaming layer 31 was attached to one surface of the laminate (heat absorbing layer 2B1 / heat absorbing layer 2A4 / heat absorbing layer 2B1) using an acrylic resin adhesive to obtain a test specimen 1-4. The content of sodium tetraborate hydrate in the heat absorbing layer 2A4 was 3.9 kg / m 2 This test specimen 1-4 has the configuration shown in FIG.
[0183] [Examples 1-5] (Test specimens 1-5) The heat absorption layer 2B1 was placed in a formwork (100 mm x 100 mm), a mixed liquid of the first constituent component of the heat absorption layer 2A1 and the second constituent component of the heat absorption layer 2A1 was poured onto the heat absorption layer 2B1, and the heat absorption layer 2B1 was laminated on top of that. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour, and then the mixture was removed from the mold to obtain a laminate of heat absorption layer 2B1 / heat absorption layer 2A1 / heat absorption layer 2B1. Furthermore, a thermal foaming layer 31 was attached to one surface of the laminate (heat absorbing layer 2B1 / heat absorbing layer 2A1 / heat absorbing layer 2B1) using an acrylic resin adhesive to obtain a test specimen 1-5. The content of sodium tetraborate hydrate in the heat absorbing layer 2A1 was 3.2 kg / m 2 This test specimen 1-5 has the configuration shown in FIG.
[0184] [Examples 1-6] (Test specimen 1-6) The heat absorption layer 2B1 was placed in a formwork (100 mm x 100 mm), and a mixed liquid of the first constituent component of the heat absorption layer 2A1 and the second constituent component of the heat absorption layer 2A1 was poured onto the heat absorption layer 2B1. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then removed from the formwork to obtain a laminate of the heat absorption layer 2B1 / heat absorption layer 2A1. Furthermore, the heat absorption layer 2B1 and the thermal foaming layer 31 were bonded in this order to the surface side of the heat absorption layer 2B1 of the laminate (heat absorption layer 2B1 / heat absorption layer 2A1) using an acrylic resin adhesive to obtain a test specimen 1-6. The content of sodium tetraborate hydrate in the heat absorption layer 2A1 was 4.2 kg / m 2 This test specimen 1-6 has the configuration shown in FIG.
[0185] [Examples 1-7] (Test specimen 1-7) A mixture of the first and second components of the heat absorption layer 2A7 was poured into a mold (100 mm x 100 mm), and a load of 1 MPa was applied to react at 40°C for 1 hour, followed by demolding to obtain a heat absorption layer 2A7. Another heat absorption layer 2A7 was obtained by the above method, and the heat absorption layer 2A7 and the heat absorption layer 2A7 were bonded together using an acrylic resin adhesive, and further the thermal foaming layer 31 was bonded together using an acrylic resin adhesive to obtain a test specimen 1-7 (heat absorption layer 2A7 / heat absorption layer 2A7 / thermal foaming layer 31). The total content of sodium tetraborate hydrate in the two heat absorbing layers 2A7 is 11.6 kg / m 2 This specimen 1-7 has the configuration shown in FIG.
[0186] [Examples 1-8] (Test specimen 1-8) A mixture of the first and second components of the heat absorption layer 2A8 was poured into a mold (100 mm x 100 mm), and a load of 1 MPa was applied to react at 40°C for 1 hour, followed by demolding to obtain a heat absorption layer 2A8. Another heat absorption layer 2A8 was obtained by the above method, and the heat absorption layer 2A8 and the heat absorption layer 2A8 were bonded together using an acrylic resin adhesive, and further the thermally foamed layer 31 was bonded together using an acrylic resin adhesive to obtain a test specimen 1-8 (heat absorption layer 2A8 / heat absorption layer 2A8 / thermal foamed layer 31). The total content of sodium tetraborate hydrate in the two heat absorbing layers 2A8 is 12.2 kg / m 2 This test piece 1-8 has the configuration shown in FIG.
[0187] [Examples 1-9] (Test specimen 1-9) A mixture of the first and second components of the heat absorption layer 2A8 was poured into a mold (100 mm x 100 mm), and a load of 1 MPa was applied to react at 40°C for 1 hour, followed by demolding to obtain the heat absorption layer 2A8. The heat absorption layer 2A8 and the thermally foamed layer 31 were bonded onto the heat absorption layer 2B1 using an acrylic resin adhesive to obtain a test specimen 1-9 (heat absorption layer 2B1 / heat absorption layer 2A8 / thermal foamed layer 31). The total content of sodium tetraborate hydrate in the heat absorption layer 2A8 is 6.1 kg / m 2 This test piece 1-9 has the configuration shown in FIG.
[0188] [Comparative Example 1-1] (Test specimens 1-10) The heat absorption layer 2B1 was placed in a formwork (100 mm x 100 mm), and a mixed liquid of the first constituent component of the heat absorption layer 2A3 and the second constituent component of the heat absorption layer 2A3 was poured onto the heat absorption layer 2B1. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then removed from the formwork to obtain a laminate of the heat absorption layer 2B1 / heat absorption layer 2A3. Furthermore, a thermally foamable layer 31 was attached to the heat absorbing layer 2A3 side of the laminate using an acrylic resin adhesive to obtain a specimen 1-10. This specimen 1-10 has an aspect shown in FIG.
[0189] [Comparative Example 1-2] (Test specimen 1-11) The heat absorbing layer 2B1 and the thermally foamable layer 31 were bonded to the heat absorbing layer 2B1 in this order using an acrylic resin adhesive to obtain a test specimen 1-11. This test specimen 1-11 has the aspect shown in FIG.
[0190] [Example 2-1] (Test specimen 2-1) The heat absorption layer 2B2 was placed in a formwork (600 mm x 450 mm), and a mixed liquid of the first constituent component of the heat absorption layer 2A1 and the second constituent component of the heat absorption layer 2A1 was poured onto the heat absorption layer 2B2. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then demolded to obtain a composite layer P21 of the heat absorption layer 2B2 / heat absorption layer 2A1. The heat absorbing layer 2B2 and the thermally foamed layer 32 were bonded together using an acrylic resin adhesive to obtain a composite layer Q21 of the heat absorbing layer 2B2 / thermally foamed layer 32. The composite layer P21 and the composite layer Q21 were laminated on the substrate 11 (substrate 11, heat absorption layer 2B2, heat absorption layer 2A1, heat absorption layer 2B2, and thermal foaming layer 32 were laminated in this order) and fixed with screws to obtain a test specimen 2-1. The content of sodium tetraborate hydrate in the heat absorption layer 2A1 was 5.1 kg / m 2 A thermocouple was placed between the substrate 11 and the heat absorbing layer 2B2 in contact with the substrate 11. This specimen 2-1 has an aspect shown in FIG.
[0191] [Example 2-2] (Test specimen 2-2) The heat absorption layer 2B1 was placed in a formwork (600 mm x 450 mm), and a mixed liquid of the first constituent component of the heat absorption layer 2A1 and the second constituent component of the heat absorption layer 2A1 was poured onto the heat absorption layer 2B1. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then demolded to obtain a composite layer P22 of the heat absorption layer 2B1 / heat absorption layer 2A1. Further, the heat absorbing layer 2B1 and the thermally foamed layer 32 were bonded together using an acrylic resin adhesive to obtain a composite layer Q22 of the heat absorbing layer 2B1 / thermally foamed layer 32. The composite layer P22 and the composite layer Q22 were laminated on the substrate 11 (substrate 11, heat absorption layer 2B1, heat absorption layer 2A1, heat absorption layer 2B1, and thermal foaming layer 32 were laminated in this order) and fixed with screws to obtain a test specimen 2-2. The content of sodium tetraborate hydrate in the heat absorption layer 2A1 was 4.2 kg / m 2 A thermocouple was placed between the substrate 11 and the heat absorbing layer 2B1 in contact with the substrate 11. This specimen 2-2 has an aspect shown in FIG.
[0192] [Example 2-3] (Test specimen 2-3) The heat absorption layer 2B1 was placed in a formwork (600 mm x 450 mm), and a mixed liquid of the first constituent component of the heat absorption layer 2A1 and the second constituent component of the heat absorption layer 2A1 was poured onto the heat absorption layer 2B1. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then demolded to obtain a composite layer P23 of the heat absorption layer 2A1 / heat absorption layer 2B1. The heat absorbing layer 2B1 and the thermally foamed layer 32 were bonded together using an acrylic resin adhesive to obtain a composite layer Q23 of the heat absorbing layer 2B1 and the thermally foamed layer 32. The composite layer P23 and the composite layer Q23 were laminated on the substrate 11 (substrate 11, heat absorption layer 2A1, heat absorption layer 2B1, heat absorption layer 2B1, and thermal foaming layer 32 were laminated in this order) and fixed with screws to obtain a test specimen 2-3. The content of sodium tetraborate hydrate in the heat absorption layer 2A1 was 4.2 kg / m 2 A thermocouple was placed between the substrate 11 and the heat absorption layer 2A1. This specimen 2-3 has the configuration shown in FIG.
[0193] [Example 2-4] (Test specimen 2-4) The heat absorption layer 2B2 was placed in a formwork (600 mm x 450 mm), a mixed liquid of the first constituent component of the heat absorption layer 2A4 and the second constituent component of the heat absorption layer 2A4 was poured onto the heat absorption layer 2B2, and the heat absorption layer 2B2 was laminated on top of that. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour, and then the mixture was demolded to obtain a composite layer P24 of heat absorption layer 2B2 / heat absorption layer 2A4 / heat absorption layer 2B2. Further, the heat absorbing layer 2B1 and the thermally foamed layer 32 were bonded together using an acrylic resin adhesive to obtain a composite layer Q24 of the heat absorbing layer 2B1 / thermally foamed layer 32. The composite layer P24 and the composite layer Q24 were laminated on the substrate 11 (substrate 11, heat absorption layer 2B2, heat absorption layer 2A4, heat absorption layer 2B2, heat absorption layer 2B1, and thermal foaming layer 32 were laminated in this order) and fixed with screws to obtain a test specimen 2-4. The content of sodium tetraborate hydrate in the heat absorption layer 2A4 was 4.8 kg / m 2 A thermocouple was placed between the substrate 11 and the heat absorbing layer 2B2 in contact with the substrate 11. This specimen 2-4 has an aspect shown in FIG.
[0194] [Example 2-5] (Test specimen 2-5) The heat absorption layer 2B2 was placed in a formwork (600 mm x 450 mm), a mixed liquid of the first constituent component of the heat absorption layer 2A5 and the second constituent component of the heat absorption layer 2A5 was poured onto the heat absorption layer 2B2, and the heat absorption layer 2B2 was further laminated on top of that. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour, and then the mixture was removed from the mold to obtain a composite layer P25 of heat absorption layer 2B2 / heat absorption layer 2A5 / heat absorption layer 2B2. Further, the heat absorbing layer 2B2 and the thermally foamed layer 32 were bonded together using an acrylic resin adhesive to obtain a composite layer Q25 of the heat absorbing layer 2B2 / thermally foamed layer 32. The composite layer P25 and the composite layer Q25 were laminated on the substrate 11 (substrate 11, heat absorption layer 2B2, heat absorption layer 2A5, heat absorption layer 2B2, heat absorption layer 2B2, and thermal foaming layer 32 were laminated in this order) and fixed with screws to obtain a test specimen 2-5. The content of sodium tetraborate hydrate in the heat absorption layer 2A5 was 6.7 kg / m 2 A thermocouple was placed between the substrate 11 and the heat absorbing layer 2B2 in contact with the substrate 11. This specimen 2-5 has an aspect shown in FIG.
[0195] [Example 2-6] (Test specimen 2-6) The heat absorption layer 2B2 was placed in a formwork (600 mm x 450 mm), and a mixed liquid of the first constituent component of the heat absorption layer 2A6 and the second constituent component of the heat absorption layer 2A6 was poured onto the heat absorption layer 2B2. A load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then demolded to obtain a composite layer P26 of the heat absorption layer 2B2 / heat absorption layer 2A6. Further, the heat absorbing layer 2B2 and the thermally foamed layer 32 were bonded together using an acrylic resin adhesive to obtain a composite layer Q26 of the heat absorbing layer 2B2 / thermally foamed layer 32. The composite layer P26 and the composite layer Q26 were laminated on the substrate 11 (substrate 11, heat absorption layer 2B2, heat absorption layer 2A6, heat absorption layer 2B2, and thermal foaming layer 32 were laminated in this order) and fixed with screws to obtain a test specimen 2-6. The content of sodium tetraborate hydrate in the heat absorption layer 2A6 was 4.6 kg / m 2 A thermocouple was placed between the substrate 11 and the heat absorption layer 2B2 in contact with the substrate 11. This specimen 2-6 has an aspect shown in FIG.
[0196] [Example 2-7] (Test specimen 2-7) A mixture of the first and second constituent components of the heat absorption layer 2A7 was poured into a formwork (600 mm x 450 mm), a load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then demolded to obtain the heat absorption layer 2A7. The heat absorption layer 2B1, the heat absorption layer 2A7, and the thermally foamed layer 32 were laminated on the substrate 11 (substrate 11, heat absorption layer 2B1, heat absorption layer 2A7, and thermally foamed layer 32 were laminated in this order) and fixed with screws to obtain a test specimen 2-7. The content of sodium tetraborate hydrate in the heat absorption layer 2A7 was 8.7 kg / m 2 A thermocouple was placed between the substrate 11 and the heat absorption layer 2B1. This specimen 2-7 has an aspect shown in FIG.
[0197] [Example 2-8] (Test specimen 2-8) A mixture of the first and second constituent components of the heat absorption layer 2A8 was poured into a formwork (600 mm x 450 mm), a load of 1 MPa was applied, and the mixture was reacted at 40°C for 1 hour. The mixture was then demolded to obtain the heat absorption layer 2A8. The heat absorbing layer 2A8, the heat absorbing layer 2B1, and the thermally foamed layer 32 were laminated on the substrate 11 (substrate 11, heat absorbing layer 2A8, heat absorbing layer 2B1, and thermally foamed layer 32 were laminated in this order) and fixed with screws to obtain a test specimen 2-8. The content of sodium tetraborate hydrate in the heat absorbing layer 2A8 was 9.2 kg / m 2A thermocouple was placed between the substrate 11 and the heat absorption layer 2A8. This specimen 2-8 has an aspect shown in FIG.
[0198] [Comparative Example 2-1] (Test specimen 2-9) The organic heat insulating material layer and the thermally foamed layer 32 were bonded together using an acrylic resin adhesive to obtain a composite layer 27 . The composite layer 27 was fixed to the substrate 11 with screws (the substrate 11, the organic heat insulating material layer, and the thermally foamed layer 32 were laminated in this order) to obtain a specimen 2-9. A thermocouple was installed between the substrate 11 and the organic heat insulating material layer. This specimen 2-9 has the configuration shown in FIG. 25.
[0199] [Comparative Example 2-2] (Test piece 2-10) The organic heat insulating material layer and the heat absorbing layer 2B1 were bonded together using an acrylic resin adhesive to obtain a composite layer . The composite layer 28 was fixed to the substrate 11 with screws (the substrate 11, the organic heat insulating material layer, and the heat absorbing layer 2B1 were laminated in this order) to obtain a specimen 2-10. A thermocouple was installed between the substrate 11 and the organic heat insulating material layer. This specimen 2-10 has the configuration shown in FIG. 26.
[0200] [Comparative Example 2-3] (Test specimen 2-11) The heat absorbing layer 2B1 and the thermally foamed layer 32 were bonded together with an acrylic resin adhesive to produce a composite layer Q29. The composite layer Q29 was fixed to the substrate 11 with screws (the substrate 11, the heat absorption layer 2B1, and the thermally foamed layer 32 were laminated in this order) to obtain a specimen 2-11. A thermocouple was installed between the substrate 11 and the heat absorption layer 2B1. This specimen 2-11 has the configuration shown in FIG. 27.
[0201] [Example 3-1] (Test specimen 3-1) The heat absorbing layer 2A7 was placed on the four side surfaces of the base material 12, which was a rectangular column, and fixed with screws. The thermally foamed layer 32 was then attached with an acrylic resin adhesive (FIG. 28), and the decorative layer 5 was then attached with a vinyl acetate resin adhesive to obtain a test specimen 3-1. A thermocouple was placed between the base material 12 and the heat absorbing layer 2A7 in contact with the base material 11. This test specimen 3-1 has the configuration shown in FIG. 29.
[0202] [Example 3-2] (Test specimen 3-2) The heat absorbing layer 2B3 and the heat absorbing layer 2A7 were laminated on the four side surfaces of the base material 12, which is a rectangular column, and fixed with screws. Furthermore, the thermally foamed layer 32 was attached with an acrylic resin adhesive (FIG. 30), and then the decorative layer 5 was attached with a vinyl acetate resin adhesive to obtain a specimen 3-2. A thermocouple was placed between the base material 12 and the heat absorbing layer 2B3. This specimen 3-2 has the configuration shown in FIG. 31.
[0203] [Example 3-3] (Test specimen 3-3) The heat absorbing layer 2A7 and the heat absorbing layer 2B3 were laminated on the four side surfaces of the base material 12, which is a rectangular column, and fixed with screws. Furthermore, the thermally foamed layer 32 was attached with an acrylic resin adhesive (FIG. 32), and then the decorative layer 5 was attached with a vinyl acetate resin adhesive to obtain a specimen 3-3. A thermocouple was placed between the base material 12 and the heat absorbing layer 2A7. This specimen 3-3 has the configuration shown in FIG. 33.
[0204] [Comparative Example 3-1] (Test specimen 3-4) An organic heat insulating layer and a thermally foamed layer 32 were attached to the four side surfaces of a rectangular pillar-shaped base material 12 using an acrylic resin adhesive to obtain a test piece 3-4. A thermocouple was installed between the base material 12 and the organic heat insulating layer.
[0205] (Layer configuration of test specimen, etc.) The stacking configuration, thickness (mm) and mass per unit area (kg / m2) of each test specimen prepared by the above method were recorded. 2) are as shown in Tables 1 to 3 below.
[0206] (Fire resistance test 1) The test specimens 1-1 to 1-11 (laminates) prepared by the above method were subjected to a fire resistance test using a cone calorimeter specified in ISO 5660. The heating intensity was 50 kW / m 2 The heating time was 90 minutes. In the fire resistance test, the temperature of the back side of the test specimen was measured during heating, and the maximum temperature reached was used for evaluation. The back side of the test specimen here refers to the side with the heat absorption layer (the side not heated). The evaluation criteria are as follows. The test results are shown in Table 1. Generally, wood begins to decompose at around 200°C and generates flammable gases, and the risk of combustion increases at temperatures above 250°C. Therefore, for practical use, an evaluation standard of AA, A, or B is preferable. (Evaluation Criteria) AA: Maximum temperature is 125℃ or less A: The maximum temperature is over 125℃ and below 150℃ B: Maximum temperature is over 150℃ and below 200℃ C: Maximum temperature is over 200℃ and below 250℃ D: Maximum temperature exceeds 250℃
[0207] (Fire resistance test 2) Each of the specimens 2-1 to 2-11 (covered structures) prepared by the above method was placed in a test furnace (facing downward so that the substrate side was facing upward), and a heating test was performed for 120 minutes according to the standard heating curve of ISO 834. The surface temperature of the wood substrate when the specimen surface was heated was measured with a thermocouple. The surface temperature was evaluated by measuring the surface temperature immediately after the 120-minute heating test and again 120 minutes after heating was stopped. The evaluation criteria are as follows. The test results are shown in Table 2. In consideration of the danger of wood combustion in practical use, the evaluation criteria of AA, A, or B are preferable as practical levels. (Evaluation Criteria) AA: 110℃ or less immediately after 120 minutes of heating, and 130℃ or less 120 minutes after heating was stopped A: Immediately after 120 minutes of heating, 110°C or higher and 150°C or lower, and 120 minutes after heating is stopped, 150°C or lower B: Immediately after 120 minutes of heating, 150°C or higher and 250°C or lower, and 120 minutes after heating is stopped, 250°C or lower C: Over 250℃ immediately after heating for 120 minutes
[0208] (Fire resistance test 3) Each of the specimens 3-1 to 3-4 (coated structures) prepared by the above method was placed vertically in a test furnace, and a heating test was performed for 90 minutes in accordance with the standard heating curve of ISO834. The surface temperature of the substrate 12 when the surface of the specimen was heated was measured by a thermocouple. The thermocouples were placed in a total of eight locations: four locations at each corner at a height of 400 mm of the substrate 12, and four locations at the center of each surface between the corners. The evaluation criteria are as follows. The test results are shown in Table 3. In consideration of the danger of wood combustion in practical use, it is preferable that the practical level is A or B in the evaluation criteria. (Evaluation Criteria) A: Immediately after 90 minutes of heating, all points are below 200℃ B: Immediately after 90 minutes of heating, all points are below 250℃ C: Immediately after 90 minutes of heating, more than one place exceeds 250℃
[0209] [Table 1]
[0210] [Table 2]
[0211] [Table 3]
[0212] From the evaluation results in Table 1 above, it was confirmed that in Examples 1-1 to 1-9 (test specimens 1-1 to 1-9), by using a laminate in which a heat absorption layer and a thermal foaming layer are laminated in sequence, the mass per unit area can be kept low, weight can be reduced, and fire resistance is also at a practical level.
[0213] On the other hand, from the evaluation results in Table 1, it was confirmed that in Comparative Example 1-1 (Specimen 1-10), the heat absorption layer of the present invention was not used, and therefore the fire resistance was not at a practical level. Also, in Comparative Example 1-2 (Specimen 1-11), the heat absorption layer of the present invention and the laminate in which the thermally foamed layer was laminated were not used, and therefore the fire resistance was not at a practical level.
[0214] From the evaluation results in Table 2 above, in Examples 2-1 to 2-8 (test specimens 2-1 to 2-8), by using a laminate in which a heat absorption layer and a thermal foaming layer are laminated in order on a wood base material, which is an organic base material, it was confirmed that the mass per unit area was kept low, the weight was reduced, workability and construction were excellent, and further, the fire resistance was at a practical level.
[0215] On the other hand, from the evaluation results in Table 2 above, it was confirmed that in Comparative Examples 2-1 to 2-3 (test specimens 2-9 to 2-11), the heat absorption layer of the present invention was not used for the wood base material, which is an organic base material, and therefore the fire resistance was not at a practical level.
[0216] From the evaluation results in Table 3 above, it was confirmed that in Examples 3-1 to 3-3 (test specimens 3-1 to 3-3), the fire resistance was also at a practical level by using a laminate in which a heat absorption layer and a thermal foaming layer were laminated in that order on a wood base material, which is an organic base material.
[0217] On the other hand, from the evaluation results in Table 3 above, it was confirmed that in Comparative Example 3-1 (Specimen 3-4), the heat absorption layer of the present invention was not used for the wood base material, which is an organic base material, and therefore the fire resistance was not at a practical level.
Claims
1. A laminate including a heat absorbing layer and a thermal foaming layer, The heat absorbing layer is formed from a binder and sodium tetraborate.
2. the binder is an organic binder, 2. The laminate of claim 1, wherein the sodium tetraborate comprises sodium tetraborate decahydrate.
3. 3. The laminate of claim 2, wherein the organic binder is provided by a polyol and an isocyanate.
4. 3. A laminate according to claim 2, wherein the organic binder is obtained from an unsaturated polyester and an unsaturated monomer.
5. 2. The laminate according to claim 1, wherein the heat absorbing layer includes at least a heat absorbing layer formed of an organic binder and sodium tetraborate, and a heat absorbing layer formed of an inorganic binder.
6. The density of the heat absorbing layer is 0.05 g / cm 3 1.5g / cm or more 3 The laminate of claim 1 , wherein the thickness is less than 1 mm.
7. The laminate according to claim 1 , wherein the thickness of the laminate is 60 mm or less.
8. The mass per unit area of the laminate is 40 kg / m 2 The laminate according to claim 1, wherein:
9. A coated structure comprising an organic substrate coated with the laminate according to any one of claims 1 to 8.
10. 10. The covered structure according to claim 9, wherein the organic substrate is a wood substrate and / or a plastic substrate.
11. The coated structure according to claim 9 , wherein the heat absorbing layer and the organic substrate are in contact with each other.
12. 10. The coated structure according to claim 9, wherein the organic substrate is a flat plate or a shaft-shaped member having a rectangular or circular cross section.
Citation Information
Patent Citations
Zooryutaikazai oyobi zooryutaikazaio mochiitenaru taikapaneru
JP1976046714A
Fire resistant construction and method of manufacturing the same, and fire resistant composition
JP2013144397A
Refractory composite structure
JP2015507562A
Thermal runaway prevention sheet
JP2018206605A
Laminate
JP2021041579A
Cited By
Laminate and coated structure
WO2026160431A1